Design, Synthesis, and Antifungal Activity of 3‐(Thiophen‐2‐yl)‐1, 5‐dihydro‐2H‐pyrrol‐2‐one Derivatives Bearing a Carbonic Ester Group. (25th November 2018) - Wang, Xiaobin; Ren, Zhengjiao; Mei, Yudong; Liu, Menghan; Chen, Min; Si, Weijie; Yang, Chunlong; Song, Yimin
Abstract : A series of 3‐(thiophen‐2‐yl)‐1, 5‐dihydro‐2 H ‐pyrrol‐2‐one derivatives bearing a carbonic ester group were designed and synthesized by integrating a thiophene nucleus and a pyrroline‐2‐one scaffold in a single molecular architecture. Their structures were confirmed by IR, 1 H‐NMR, EI‐MS, and elemental analyses, and their antifungal activities against Fusarium graminearum (Fg), Rhizoctorzia solani (Rs), and Botrytis cinerea (Bc) were evaluated. The antifungal bioassays indicated that some title compounds exhibited desirable antifungal effects against the tested fungi. Strikingly, the title compounds 4i, 4k, 4n, and 4o showed obvious antifungal activities against Rs, with corresponding EC50 values of 35.26, 33.56, 23.90, and 30.48 μg/mL, respectively, which are better than that of hymexazol (37.86 μg/mL). These results indicated that 3‐(thiophen‐2‐yl)‐1, 5‐dihydro‐2 H ‐pyrrol‐2‐one derivatives bearing a carbonic ester group can serve as potential structural templates in the search for novel high‐efficient fungicides. Abstract :